2009
DOI: 10.1088/0953-8984/21/48/485001
|View full text |Cite
|
Sign up to set email alerts
|

Theory of powdery rubber wear

Abstract: Rubber wear typically involves the removal of small rubber particles from the rubber surface. On surfaces with not too sharp roughness, e.g. most road surfaces, this involves (slow) crack propagation. In this paper I shall present a theory of mild rubber wear. I shall derive the distribution of wear particle sizes Φ(D), which is in excellent agreement with experiment. I shall also show that the calculated wear rate is consistent with experimental data for tire tread block wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…Two parameters contribute to the friction of rubbers, in the form of adhesion and hysteresis friction. While the adhesion component is responsible for the friction of elastomers, the deformation mechanism involves complete dissipation of energy in the contact area . The protuberance of larger abrasives and low mechanical properties (high 1/(se)) lead to the increase of TBU by the increase of the adhesive friction and deformation of the rubber, respectively.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Two parameters contribute to the friction of rubbers, in the form of adhesion and hysteresis friction. While the adhesion component is responsible for the friction of elastomers, the deformation mechanism involves complete dissipation of energy in the contact area . The protuberance of larger abrasives and low mechanical properties (high 1/(se)) lead to the increase of TBU by the increase of the adhesive friction and deformation of the rubber, respectively.…”
Section: Resultssupporting
confidence: 55%
“…While the adhesion component is responsible for the friction of elastomers, the deformation mechanism involves complete dissipation of energy in the contact area. 40,44 The protuberance of larger abrasives and low mechanical properties (high 1/(se)) lead to the increase of TBU by the increase of the adhesive friction and deformation of the rubber, respectively. With the increase of the abrasive size, the real contact area and applied stress on surface of rubber increase that lead to the increase of participation of adhesive friction and deformation in friction, respectively.…”
Section: Temperature Buildup (Tbu)mentioning
confidence: 99%
“…Rubber friction is a topic of huge practical importance, e.g., for tires, rubber seals, wiper blades, conveyor belts and syringes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Many experiments have been performed with a hard spherical ball rolling on a flat rubber substrate [15,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…This is evident, when comparing the specific wear rates which differ by even two decades of magnitude. This can be explained by the concept of the crack mean-free path, using theory of powdery rubber wear [32]; it has been suggested that reducing the crack mean-free path results in reduction of the wear rate. Unreinforced rubber compound, because of lack of (strong) inhomogeneities which can scatter the crack tip and reduce the crack mean-free path, has a very bad wear resistance.…”
Section: Discussionmentioning
confidence: 99%